Video Coding Using Embedded Wavelet Packet Transform and Motion Compensation - Cheng, Po-Yuen; Li, Jin; Kuo, C.-C. Jay (SPIE: Visual Information Processing V, Orlando, FL, 1996)
In this paper, we propose a hybrid video coder using the wavelet packet transform and motion compensation. To reduce the computational complexity of the wavelet packet decomposition, a novel criterion based on the rate-distortion function is proposed. After the wavelet packet transform, the successive quantization scheme and the adaptive arithmetic coder are applied for lossy wavelet coefficient compression. Extensive experiments have been carried to compare the embedded wavelet packet coder with the MPEG standard and the embedded pyramid wavelet coder. The proposed wavelet packet transform method has the best performance in terms of both visual quality and PSNR measurement.